Global trends in the surgical management of gastric cancer - Woo, Yanghee; Son, Taeil; Obama, Kazutaka (Translational Gastroenterology and Hepatology, 2019)
Gastric adenocarcinoma (GC) poses a formidable global cancer care challenge highlighted by geographical heterogeneity of the disease and differing treatment patterns worldwide. For the past three decades, exciting controversies in the timing and type of perioperative therapies, heated debates on the importance of the number and extent of lymphadenectomy, and pioneering adoption of disruptive surgical technology have energized the field of GC surgery.